Artificial Intelligence in Prosthodontics: Current Applications and Future Avenues: A Narrative Review - Rishu Koul; Guruprasada Upadhyay; Deepak Kalia; Kamal Verma (Journal of Primary Care Dentistry and Oral Health)
Artificial intelligence (AI) is becoming increasingly popular globally due to its substantial influence in the fields of research and innovation. The utilization of AI in prosthodontics has had a substantial growth in recent years. AI is employed in various aspects of dentistry, including diagnosing, making decisions, predicting outcomes, planning treatments, selecting tooth shades, designing restorations, mapping preparation finishing lines, optimizing casting manufacturing, predicting facial changes in patients with removable prostheses, and determination of treatment outcomes of obstructive sleep apnea, which have a pivotal role in oral health care. The incorporation of AI into prosthodontics has the potential to improve the accuracy and precision of dental procedures. Nevertheless, the scarcity of datasets significantly hinders its practical implementation.